Answer:
y= - 3cosx - 2
Explanation:
Our max here is at 1, and the minimum is at - 5
The distance between the x-axis and these points are 1 and 5. 5 + 1/2 = 6/2 = 3, our amplitude. But let's double check. Our middle point is - 2 so...
- 5 - (- 2) = - 5 + 2 = - 3
The amplitude is rather - 3.
f(x) = Acos(Bx + C) + D
Using this we know B = 0, D = - 2 (the middle point), C = 0, and A = - 3 (amplitude). B = 0, and C = 0, as there is no horizontal/vertical shift
f(x) = Acos(Bx + C) + D
f(x) = - 3cosx + (- 2)
f(x) = - 3cosx - 2